Digital co-creation : Mission (im)possible? - Kirjavainen, Hanna; Jalonen, Harri (Routledge, 2022)
This chapter discusses the promises and pitfalls of digital co-creation. Drawing on the emerging literature on co-creation of public services the chapter seeks to identify the enabling factors helping bridge the gap between service providers and service users. Of particular interest is how digital means can be used for engaging vulnerable people. The chapter focuses on three technologies: open data, social media, and artificial intelligence. Pros and cons for each of them are discussed. The empirical part of the chapter consists of showcasing some digital initiatives conducted in the research project. The chapter ends with a suggestion that digitally enabled co-creation should be understood as a process consisting of three consecutive phases: sensing, sensemaking, and seizing. Sensing is referred to collecting and organizing data from social media and other sources. It helps a public service organization understand what is happening in the environment. Sensemaking aims to add value to the data extracted in the sensing phase. It links causes to consequences by providing answers to questions of how and why something is happening. Seizing focuses on the change and creating new actionable solutions and opportunities. The outcome of seizing is learning from the data in a way that enables organizations to influence events as they happen.
Keywords: fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|